Pengaruh Perencanaan Program Kesiswaan Terhadap Pengembangan Karakter Siswa di Sekolah Menengah Pertama - Febrinal, Dian; Zahara, Sri; Asmendri, Asmendri; Sari, Milya; Khairani, Majidah (Indo-MathEdu Intellectuals Journal, 2024)
The student program, which includes extracurricular activities, student organizations, and social activities, plays an important role in supporting the character development of students. This research aims to analyze the influence of student participation in extracurricular programs on character development at SMPN Sijunjung. This study employs a quantitative method with a survey approach and cross-sectional design. The research sample consists of 200 students randomly selected from several middle schools in Sijunjung. Data were collected using a Likert scale questionnaire to measure students' perceptions of their participation in student programs and character development. Data analysis was conducted using descriptive and inferential statistical tests, specifically Pearson correlation, using SPSS software. The research results indicate that students' participation in student programs is positively and significantly related to their character development, with a Pearson correlation value of r = 0.65. Sports extracurricular programs have the strongest influence on character development, followed by student organizations. More frequent participation in student activities is also associated with a higher level of character development. This research suggests the need for an improvement in the quality of student programs and stronger support from teachers, parents, and school authorities to maximize the positive impact on students' character